HARMONISASI HUKUM: PENGATURAN PEMILU SERENTAK DAN PERLINDUNGAN HUKUM, ANALISIS YURIDIS TERHADAP KEMATIAN KPPS TAHUN 2019 - Kristian, Kristian; Firdaus, Sunny Ummul (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2020)
The purpose of this research is to know about the rule of KPPS’ member which is included in rule of law about Pemilihan Umum Serentak which happened in 2019. This research is a perspective normative research. The types of legal materials used in the research are primary legal materials and secondary legal materials. The technique of collecting legal materials uses the literature study technique. The 2019’s Pemilihan Umum Serentak was a party of democracy which should be able to bring prosperity to Indonesian. However, the reality was hundred of the KPPS’ members fell ill and even died. This happened because of the woking load and time were not in accordance with human working abilty in general. The death of hundred of KPPS’ members made Indonesia grieved, especially when Indonesia is designed as a welfare state in accordance with the mandate of Pancasila. When it is viewed from the point of view of establishing a good constitution so that the welfare of the KPPS’ member materialized, then changes or even adding the article about the welfare of KPPS’ member are needed whether it is in constitution or in MK’ decision.